Penguatan keterampilan regulasi diri melalui konseling realitas pada mahasiswa dengan risiko drop out - Hapsari Puspita Rini; Ni Putu Rizky Arnani (Procedia : Studi Kasus dan Intervensi Psikologi, 2026)
Completing college studies on time is every student’s hope. However, sometimes students lack a clear understanding of what they need to do to graduate on time. This study aims to determine the role of reality counseling in improving self-regulation in students working on their theses. The method used was an experimental method with a single-subject design. Assessments were conducted using observation, interviews, IST tests, and EPPS. The subject of this study was a student working on a thesis and facing a graduation deadline. Reality counseling interventions based on choice theory are expected to help individuals understand that their desires are their personal responsibility. The reality counseling approach trains individuals to make effective choices to achieve goals based on the WDEP concept (wants, direction, self evaluation, planning). After four counseling sessions, the subject showed improved self-regulation, characterized by the ability to clearly define desires (wants), identify work directions to achieve goals (direction), evaluate attitudes, behaviors, and thoughts to achieve goals (evaluation), and create plans to achieve goals based on their desires (planning). The subject was finally able to complete the thesis and graduate before the final deadline for the lecture.